2013
DOI: 10.1620/tjem.229.87
|View full text |Cite
|
Sign up to set email alerts
|

<i>Listeria monocytogenes</i> Inoculation Protects Mice against Blood-Stage <i>Plasmodium yoelii</i> Infection

Abstract: Listeria monocytogenes (Lm) has been used as the adjuvant or vector for tumor and viral vaccine for its capability of eliciting all aspects of cell-mediated immunity including T cell activation and interferon-gamma (IFN-γ) production. These effector components play critical roles in the protection against Plasmodium infection in both human malaria and mouse models. Therefore, immune response induced by Lm infection may benefit the defense against malaria. To test this hypothesis, we employed blood-stage Plasmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Worms [Schistosoma sp (Hartgers & Yazdanbakhsh, 2006;Waknine-Grinberg et al, 2010;Bucher et al, 2011;Wang et al, 2013Wang et al, , 2014, Litomosoides sigmodontis (Karadjian et al, 2014), and Heligmosomoides polygyrus (Su et al, 2005)] and bacteria [Mycobacterium tuberculosis (Li & Zhou, 2013), Listeria monocytogenes (Qi et al, 2013), and Salmonella (Cunnington et al, 2012)] have been shown to alter the pathological outcome of malaria infection through bystander regulation of the host immunity. Specific to the PbA-ECM model, the mechanisms leading to ECM protection during co-infection were mostly due to the suppression of the pro-inflammatory response induced by the heterologous pathogen, which occurs from 4 days post-Plasmodium infection onwards.…”
Section: Discussionmentioning
confidence: 99%
“…Worms [Schistosoma sp (Hartgers & Yazdanbakhsh, 2006;Waknine-Grinberg et al, 2010;Bucher et al, 2011;Wang et al, 2013Wang et al, , 2014, Litomosoides sigmodontis (Karadjian et al, 2014), and Heligmosomoides polygyrus (Su et al, 2005)] and bacteria [Mycobacterium tuberculosis (Li & Zhou, 2013), Listeria monocytogenes (Qi et al, 2013), and Salmonella (Cunnington et al, 2012)] have been shown to alter the pathological outcome of malaria infection through bystander regulation of the host immunity. Specific to the PbA-ECM model, the mechanisms leading to ECM protection during co-infection were mostly due to the suppression of the pro-inflammatory response induced by the heterologous pathogen, which occurs from 4 days post-Plasmodium infection onwards.…”
Section: Discussionmentioning
confidence: 99%
“…major footpad lesion development [ 40 ]. Prior infection with either Listeria monocytogenes or Mycobacterium tuberculosis can protect from subsequent lethal infection from Plasmodium yoelii [ 41 , 42 ]. In each instance, the establishment of protection against the secondary infection was attributed to the production of pro-inflammatory cytokines by the first pathogen [ 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some cases of human Malaria and VL co-infection were described in the past and recently in different parts of the world ( Yoeli, 1948 ; Ab Rahman and Abdullah, 2011 ; van den Bogaart et al, 2012 , 2014 ; Bin Mohanna, 2015 ), demonstrating that co-infection may occur more frequently than we would expect. An increasing amount of evidence shows that co-infections may affect the natural outcome and progression of diseases due to the modulation of immune response ( La Flamme et al, 2002 ; Kolbaum et al, 2012 ; Qi et al, 2013 ; van den Bogaart et al, 2014 ). In the present study, we established a co-infection model of American CL and a non-lethal murine Malaria and demonstrated that co-infection is able to affect the pathogenesis and outcome of both diseases.…”
Section: Discussionmentioning
confidence: 99%